2013
DOI: 10.1118/1.4812415
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel 2D array dosimeter for patient‐specific quality assurance with volumetric arc therapy

Abstract: The OCTAVIUS 4D system has some unique characteristics that can potentially improve the patient specific pretreatment IMRT QA data collection and analysis. The ability of the software to reconstruct from the measurements the true 3D dose distribution in the phantom, provides a unique perspective for the medical physicist that evaluates a patient's QA plan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 13 publications
(14 reference statements)
3
45
0
1
Order By: Relevance
“…Finally, the comparison between the absolute dose and the dose measured by the central chamber of the array, assessed during the commissioning of the phantom for the K user determination, furnished worse agreement than what was reported in the literature (about 5% difference for both the LINACs vs 1–2% in Stathakis et al)16, probably due to array‐related characteristics. However, it was found that the K user was comparable with the K cross , obtained by the comparison with the TPS expected value (Δ ≤ 1%).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Finally, the comparison between the absolute dose and the dose measured by the central chamber of the array, assessed during the commissioning of the phantom for the K user determination, furnished worse agreement than what was reported in the literature (about 5% difference for both the LINACs vs 1–2% in Stathakis et al)16, probably due to array‐related characteristics. However, it was found that the K user was comparable with the K cross , obtained by the comparison with the TPS expected value (Δ ≤ 1%).…”
Section: Discussionmentioning
confidence: 61%
“…The 2D‐Array together with Octavius ® ‐4D are widely described in the literature 1, 16. Briefly, the 2D‐Array consisted in a matrix of 729 vented ionization chambers distant 10 mm from center to center, embedded in a 27 × 27 array.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, direct comparison of the planned and deliverable DVHs exhibits higher sensitivity and specificity, and is expected to be more clinically meaningful and intuitive to both the physician and the physicist 7 , 10 , 11 . Semiempirical volumetric dose reconstruction, based on the array measurements, was previously reported on geometrical phantoms 12 , 13 , 14 , 15 and patient CT datasets 16 , 17 . Following this trend, a recently released Delta 4 (ScandiDos AB, Uppsala, Sweden) software module called Anatomy was purchased at our clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Different QA measurement techniques in IMRT exist, making use of 2D detector array [5][6][7][8], single ion chamber in phantom for point dose measurements [9][10][11] or using specific phantoms with 2D dose measurement devices and 3D dose reconstruction software [12][13][14]. One disadvantage of these approaches is that measurements are generally compared with calculations by the TPS and it is difficult to give interpretation and to address the deviations between calculated and measured doses to failures of the accelerator performance or to the calculation algorithm.…”
Section: Introductionmentioning
confidence: 99%